Uncertainty of the optimum influence factor levels in multicriteria optimization using the concept of desirability - Heike Trautmann; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
The Desirability Index (DI) is a widely used method for multicriteria optimization in industrial quality control, by which optimal levels of the process influencing factors are determined in order to archieve maximum process quality. In practice however situations may occur in which slight changes of these factor levels lead to lower production costs or to facilitation of the production process and therefore would be preferred. In this paper an innovative approach for measuring the effect of these changes on the DI based on its distribution is introduced.
Keywords: 519; Multikriteria-Verfahren; Qualitätsmanagement; Theorie